The Operation Performance Evaluation and Maintenance of Bandar Sidoras Irrigation System in Percut Sei Tuan District Deli Serdang Regency - Ardelimas ARS; Sumono Sumono; Adian Rindang (Universitas Sumatera Utara, 2016)
Evaluation of the performance of irrigation system is one way to describe the circumstances and characteristics of an irrigation system. This study aims to evaluate the performance of operation and maintenance of Bandar Sidoras irrigation system. Some of the indicators used to determine the performance of the irrigation system were: functional performance and network infrastructure of irrigation, water sufficiency level, the level of accuracy of the provision of water, management of government institution, the availability of fund, human resources and farmer institutional performance. The results showed that the level of accuracy was very appropriate water supply, the management of government institution was very good, the farmer institution performance was very good each with the value of 4, functional performance and irrigation network infrastructure was well, the adequacy of water was sufficient, the availability of funding was adequate , and human resources were adequate each with the value of 3. in general, the performance of operation and maintenance of the Bandar Sidoras irrigation system categorized very well with a value of 3.36. Keywords: Evaluation of the performance, operation and maintenance, irrigation system, Bandar Sidoras